Translating the “Dead Indian”: Kent Monkman, Miss Chief Eagle Testickle, and the Painting of the American West - Perry, Nicole (Imaginations)

(untitled) (York University, 2020)
This article examines the work of Kent Monkman, an artist of Cree ancestry, and his Indigenous interventions into art of the American West. Known for his provocative and highly sexualized genre, Monkman, along with his gender fluid alter ego and companion, Miss Chief Eagle Testickle, have been upsetting the art world for more than a decade. By using Thomas King’s (Cherokee) concept of the “Dead Indian”, I examine how Monkman’s work revitalises Indigenous histories and places them in the centre of the paintings by the 19th-century German-American artist of the American West, Albert Bierstadt. By repurposing the scene, Monkman translates the images from anachronistic settler-colonial narratives and uses these images from the past to highlight Indigenous narratives of the American West.